Ассоциации полиморфизмов гена DRD3 с болезнью Паркинсона; Журнал неврологии и психиатрии им. C.C. Корсакова; Т. 116, № 5 - Иванова С. А. Светлана Александровна; Алифирова В. М. Валентина Михайловна; Жукова И. А. Ирина Александровна; Бойко А. С. Алексей Станиславович; Федоренко О. Ю. Ольга Юрьевна; Жукова Н. Г. Наталья Григорьевна; Бохан Н. А. Николай Александрович (Экспериментально-теоретические вопросы, 2016)
Заглавие с экрана